Ekspansi Termal, Oxygen Content, dan Sifat Elektrokimia Oksida SmBa0.5Sr0.5Co2O5+δ (70%) + SDC (30%) Sebagai Katoda SOFC - Adi Subardi; Yen-Pei Fu (Jurnal Riset Kimia, 2022)
The thermal properties of the double perovskite SmBa0.5Sr0.5Co2O5+δ (70%) + SDC (30%) have been investigated as potential cathodes for intermediate-temperature solid oxide fuel cells (IT-SOFC). This study also includes the oxygen content and electrochemical performance of long-term tests carried out to evaluate the electrochemical stability. Cathode powder is fabricated by a simple and relatively inexpensive solid-state reaction. Oxygen content decreased gradually from room temperature to 800oC by 18.3%. Doping 30% SDC into SBSC oxide can reduce the thermal expansion coefficients (TEC) value from 19.80 x 10-6 (K-1) to 18.17 x 10-6 (K-1) or a decrease of 8.23%. The activation energy (Ea) identified by the electrochemical impedance spectroscopy (EIS), low field (LF), and high field (HF) techniques were 125.3 kJ mol-1, 60.6 kJ mol-1, and 62.5 kJ mol-1, respectively. The SBSC73|SDC|SBSC73 symmetric cell test for 96 hours at 600oC showed an increase in the average polarization resistance value of 0.30% h-1. The cathode grains are evenly distributed with a size of 2-3 µm and tend to be porous. These results exhibit that SmBa0.5Sr0.5Co2O5+δ (70%) + SDC (30%) is a promising cathode material for IT-SOFCs.